Development Probiotic Drink of Siwalan Sap Ready to Drink Using Lactobacillus acidophilus FNCC0051, Lactobacillus plantarum FNCC0027, and Bifidobacterium breve BRL131 - Anggraeni, Citra Dwi Wahyu; Sri Winarti; Luqman Agung Wicaksono (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Siwalan sap is highly perishable due to its elevated sugar content, which promotes spontaneous fermentation shortly after collection. Converting siwalan sap into a probiotic beverage offers a promising alternative for extending shelf life and diversifying its utilization. This study aimed to see how different fermentation times and amounts of starter affect the physical and taste qualities of probiotic siwalan sap and to find the best combination of these factors. A factorial completely randomized design (CRD) was applied, comprising two factors: starter concentration (3%, 6%, and 9%) and fermentation time (16, 20, and 24 hours), with three replications. Data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level, followed by Duncan’s Multiple Range Test (DMRT) for significant results. Both factors significantly influenced total lactic acid bacteria (LAB), total titratable acidity, pH, reducing sugar content, total soluble solids, and organoleptic attributes (taste, aroma, and color). The best formulation was achieved with a 3% starter concentration and 20 hours of fermentation, yielding an LAB count of 8.751 log CFU/mL, pH of 4.07, a titratable acidity of 0.750%, a reducing sugar of 1.39 mg/100 mL, and total soluble solids of 17.167°Brix. Sensory evaluation indicated moderate acceptance with scores of 3.2 (taste), 3.35 (aroma), and 3.6 (color) on a 5-point hedonic scale. Contribution to Sustainable Development Goals (SDGs): SDG 3 – Good Health and Well-beingSDG 9 – Industry, Innovation, and InfrastructureSDG 12 – Responsible Consumption and ProductionSDG 13 – Climate Action: